Commodification and Spectacle in Architecture : A Harvard Design Magazine Reader - Frampton, Kenneth; Saunders, William S. (Book collections on Project MUSE., 2005)
More than ever, architectural design is seen as a means to promote commercial goals. Bringing together an impressive and varied group of critics and practitioners, this collection will help to sharpen the discussion of how design can respond to our hypercommodified culture.